If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2x + 63 = -49 + 6x Reorder the terms: 63 + -2x = -49 + 6x Solving 63 + -2x = -49 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 63 + -2x + -6x = -49 + 6x + -6x Combine like terms: -2x + -6x = -8x 63 + -8x = -49 + 6x + -6x Combine like terms: 6x + -6x = 0 63 + -8x = -49 + 0 63 + -8x = -49 Add '-63' to each side of the equation. 63 + -63 + -8x = -49 + -63 Combine like terms: 63 + -63 = 0 0 + -8x = -49 + -63 -8x = -49 + -63 Combine like terms: -49 + -63 = -112 -8x = -112 Divide each side by '-8'. x = 14 Simplifying x = 14
| 76=15.7xh^2 | | 10-x=65 | | 2x+27=2x-11 | | 4b+-8=2b+6-4b+13 | | 0=-16t^2+0t+64 | | n+0.6+n=n+0.1+2n | | 7.5+1x=2.5x | | Y/12=17/13 | | 12x+(30-2x)+12x=144 | | 7x+5x-6=2x+6 | | 62735/628358=x | | 15=5(n-8) | | log(7)(6x-5)=2 | | 4x-21=x+21 | | 17+x=-8 | | 72+19362/56=x | | 9/10 | | -15=x+20 | | 6x+5=x | | t/16=30/36 | | 5(x+1)+6(x+6)=60 | | -2w^2-5w-52=0 | | -2x+15=-60+3x | | p^2-8p+16= | | 5w-2w^2-52=0 | | 4y+7=4y+5 | | 9p^2-8p-1= | | 4m^2+20m+21= | | 3x=18-3x/2 | | 6x+7=13+2x | | 7k^2+4k-3= | | 16+6x=3x-20 |